Hubungan Tingkat Pengetahuan dan Sikap dalam Upaya Menjaga Kesehatan Gigi dan Mulut pada Wali Murid TK di Kecamatan Jelbuk Kabupaten Jember - Maharani, Rani; Kiswaluyo, Kiswaluyo; Handayani, Ari Tri Wanodyo (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2024)
Based on Basic Health Research Data (RISKESDAS) in 2018, the number of dental and oral diseases in Indonesia was 57.6% while the number of visits to the dental clinic was only 45.3%. As a result, in order to avoid disease, guardians must understand and apply efforts to maintain dental and oral health from an early age. These efforts can be influenced by the level of knowledge and the level of individual attitudes. The data is in line with the condition of Jelbuk District, Jember Regency, in 2020 the total visits to the dental clinic are still relatively low compared to existing dental and oral health cases. The aim of this research is to determine the level of knowledge, the level of attitude and analyzing the relationship between the level of knowledge and the level of attitude in an effort to maintain dental and oral health in the kindergarten guardians in Jelbuk District, Jember Regency. This research used analytic observational method with a cross sectional design. There are 3 samples in this study including Dharma Wanita Kindergarten, Al Baiturrahmah Kindergarten, and Gemilang Kindergarten. The data obtained were analyzed by the Kendall tau correlation test. The characteristics of the respondents include the average gender of women aged 20-30 years with the latest education level of Junior High school and Senior High school and the majority work as housewives. The level of knowledge and level of attitude of respondents in an effort to maintain dental and oral health is in the good category. The level of knowledge and level of attitude in an effort to maintain dental and oral health for the guardians of kindergarten students in Jelbuk District, Jember Regency are mostly in the good category and there are some belonging to the less category and the relationship between the level of knowledge and attitude is significant, strong and unidirectional.